Measurement of the Performance Level of Long-Term Services - Kasperowicz, Anna (Pomiar stopnia zaawansowania usług długoterminowych, 2011)
The paper presents characteristic features of services which, pursuant to the Polish balance sheet law, are treated as long-term services. Subsequently, the methods of determining the performance level of the service in progress as of the balance sheet day are presented based on the example of numbers, and the circumstances in which they ought to be applied are described. The results of the comparison of various methods are presented visually in the conclusion.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 177, s. 29-38
Keywords: long-term services; performance level